2010
DOI: 10.1038/onc.2010.296
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated DNA replication in E2F1- and E2F2-deficient macrophages leads to induction of the DNA damage response and p21CIP1-dependent senescence

Abstract: E2F1-3 proteins appear to have distinct roles in progenitor cells and in differentiating cells undergoing cell cycle exit. However, the function of these proteins in paradigms of terminal differentiation that involve continued cell division has not been examined. Using compound E2F1/E2F2-deficient mice, we have examined the effects of E2F1 and E2F2 loss on the differentiation and simultaneous proliferation of bone-marrow-derived cells toward the macrophage lineage. We show that E2F1/ E2F2 deficiency results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…P21, a cyclin-dependent kinase 1A inhibitor, is usually activated by DNA damage [16]. In this study, BK treatment significantly prevented p21 upregulation induced by H 2 O 2 , and prevented DNA damage induced by H 2 O 2 in H9C2 cells, indicating that BK inhibited oxidative stress mediated senescence induced by H 2 O 2 in H9C2 cells.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…P21, a cyclin-dependent kinase 1A inhibitor, is usually activated by DNA damage [16]. In this study, BK treatment significantly prevented p21 upregulation induced by H 2 O 2 , and prevented DNA damage induced by H 2 O 2 in H9C2 cells, indicating that BK inhibited oxidative stress mediated senescence induced by H 2 O 2 in H9C2 cells.…”
Section: Discussionsupporting
confidence: 55%
“…H9C2 cells were treated as described before with H 2 O 2 and BK, and 24 hours after treatment, DNA damage was determined with a commercially available kit for single cell electrophoresis, the so-called Comet Assay, and the detailed protocol was described as before [16].…”
Section: Methodsmentioning
confidence: 99%
“…Similar findings have been reported for differentiating monocyte and intestinal epithelial cells. 13,17 However, the cell fates in these cases are different from those observed in pancreatic tissue, as monocyte progenitor cells lacking E2F1/2 result in senescence, and intestinal progenitor cells lacking E2F1-3 lead to p53-independent apoptosis. The mechanism that leads to replication stress in DKO cells is still unknown, and it would be interesting to determine whether it involves illegitimate replication origin firing and fork stalling, as shown for replication stress caused by overexpression of Cdt1 33 or by aberrant CDK activity 34 in some cell types.…”
Section: E2f-p53 Regulatory Axis In Tissue Homeostasismentioning
confidence: 99%
“…16 By contrast, targeted inactivation of these E2Fs revealed their essential role in sustaining quiescence in hematopoietic cells, 11 in supporting survival of progenitor cells 16 or in facilitating exit from the cell cycle in differentiating cells. 13,17 However, the mechanisms by which E2F1 and E2F2 accomplish such diverse functions remain unresolved.…”
mentioning
confidence: 99%
“…57 Recent reports have also concluded that acceleration of the cell cycle by Cyclin E can cause DNA damage. 59,60 Interestingly, in our experiments, causing DNA damage in keratinocytes with genotoxic agents such as doxorubicin induced p53 and terminal differentiation. As discussed above, we have shown that a direct block of mitosis rapidly results in terminal differentiation.…”
mentioning
confidence: 99%